2017
DOI: 10.1002/glia.23153
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‐7116‐5p in microglia by MPP+ sensitizes TNF‐α production to induce dopaminergic neuron damage

Abstract: Activation of microglia resulting in exacerbated inflammation expression plays an important role in degeneration of dopaminergic (DA) neurons in the pathogenesis of Parkinson's disease (PD). However, how this enhanced inflammation is induced in microglia remains largely unclear. Here, in the mouse PD model induced by 1-methyl-4-phenyl-1,2,3,6-tetra hydropyridine (MPTP), we found that miR-7116-5p in microglia has a crucial role in this inflammation. 1-methyl-4-phenylpyridinium (MPP ) is uptaken by microglia thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…Therefore, we evaluated the miRNA expression profile in C-MSC and C-MSC-Exo through miRNA microArray. Our results showed that miR-7116-5p is the most enriched, abundant miRNA in C-MSC-Exo compared to C-MSC, A report has shown that inhibition of miR-7116-5p level sin microglia enhances TNF-α production and inflammation, which lead to neuron damage [35], however, there is no report about the function of miR-7116-5p in cardiovascular and muscle systems. Bioinformatics pathway analysis shows that miR-7116-5p negatively regulates protein polyubiquitination.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, we evaluated the miRNA expression profile in C-MSC and C-MSC-Exo through miRNA microArray. Our results showed that miR-7116-5p is the most enriched, abundant miRNA in C-MSC-Exo compared to C-MSC, A report has shown that inhibition of miR-7116-5p level sin microglia enhances TNF-α production and inflammation, which lead to neuron damage [35], however, there is no report about the function of miR-7116-5p in cardiovascular and muscle systems. Bioinformatics pathway analysis shows that miR-7116-5p negatively regulates protein polyubiquitination.…”
Section: Discussionmentioning
confidence: 81%
“…Work in the MPTP model of PD provided compelling evidence that MPTP kills in both a cell‐autonomous manner through neuronal production of nitric oxide (NO) and activation of parthanatos and a non‐cell‐autonomous mechanism, through microglia production of NO through inducible NO synthase . Consistent with this notion, it was recently shown that MPP + can enter microglia through cation transporters, inducing oxidative stress and inflammation that ultimately exacerbate dopaminergic neurodegeneration . Growing recognition that glial involvement cannot be discounted in neuropathological investigations has thus inspired a reconsideration and examination of existing literature on PD models and mechanisms.…”
Section: Astrocytes: Claiming a Starring Rolementioning
confidence: 99%
“…49 Consistent with this notion, it was recently shown that MPP + can enter microglia through cation transporters, inducing oxidative stress and inflammation that ultimately exacerbate dopaminergic neurodegeneration. 50 Growing recognition that glial involvement cannot be discounted in neuropathological investigations has thus inspired a reconsideration and examination of existing literature on PD models and mechanisms.…”
Section: Astrocytes: Claiming a Starring Rolementioning
confidence: 99%
“…Microglial activation and inhibition of microglial activation is tightly regulated by a number of microRNAs including pro-inflammatory mir-155 and mir-204 as well as anti-inflammatory mir-203, mir-181c and mir-424 (Cardoso et al, 2012; Li L. et al, 2015). More recently, using the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse PD model, a study has shown that 1-methyl-4-phenylpyridinium (MPP + ) downregulates mir-7116-5p in microglia and potentiates TNF-α production and inflammatory responses leading to DA neuron damage (He et al, 2017). …”
Section: Introductionmentioning
confidence: 99%